A coach perspective on the use of planned disruptions in high-performance sports - Kegelaers, J.; Wylleman, P.; Oudejans, R. R. D. (Sport, Exercise, and Performance Psychology, 2020)
In elite sports, a case is increasingly made for the structural inclusion of what we label as planned disruptions. These are structured and deliberate training activities whereby athletes are exposed to increased and/or changing demands under controlled circumstances. Despite the growing body of evidence in support of planned disruptions (Sarkar & Fletcher, 2017), there is a lack of knowledge on which strategies coaches use in an applied context and why they use them. The present study, therefore, aimed at exploring the different types of planned disruptions high-performance coaches use and the desired outcomes of these disruptions. To this end, thematic analysis (Braun, Clarke, & Weate, 2016) was used to analyze semistructured interviews with 9 talent development and elite-level coaches (Mage = 42.9, SD = 8.3; 6 male, 3 female). Results indicated that coaches use a combination of 9 types of planned disruptions (i.e., location, competition simulation, punishments and rewards, physical strain, stronger competition, distractions, unfairness, restrictions, and outside the box). These strategies were used to familiarize athletes to pressure, create awareness, develop or refine personal resources, and promote team processes. Three additional themes emerged, namely, the surprise use of planned disruptions, periodization, and the impact on personal relationships. The findings in the present study can guide further applied and theoretical explorations of the use of planned disruptions.